2016
DOI: 10.4236/fmar.2016.43007
|View full text |Cite
|
Sign up to set email alerts
|

A Human Skull with a Tripartite Inca Bone: A Case Report

Abstract: An adult human skull was discovered in a college osteological collection presenting with two Inca bones. Inca bones or interparietal (supernumerary) bones are rarely seen among dry human skulls. Their frequency of presentation is much less than that of sutural or Wormian bones. Inca bones or interparietal (supernumerary) bones are accepted as normal variants most often found in the occipitoparietal region of the skull. Their characteristic shape, a triangle, resembles a monument design of the Inca tribe of Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The highest percentage of 10% was noted in the West African population with the Japanese being next highest at 4.4%. (9) The geographical and ethnographical pattern of incidence of Inca bones shows a definite topographical and racial predilection and thus a possible genetic inheritance. Pedigree studies showed that the Inca bone is inherited as dominant trait with 50% penetrance and suggested genetic background for occurrence of Inca bone.…”
Section: Discussionmentioning
confidence: 99%
“…The highest percentage of 10% was noted in the West African population with the Japanese being next highest at 4.4%. (9) The geographical and ethnographical pattern of incidence of Inca bones shows a definite topographical and racial predilection and thus a possible genetic inheritance. Pedigree studies showed that the Inca bone is inherited as dominant trait with 50% penetrance and suggested genetic background for occurrence of Inca bone.…”
Section: Discussionmentioning
confidence: 99%